Shaping Character Through Faith: Evaluating Religious Culture Reinforcement in Schools - Erbayanti, Erbayanti; Thaha, Hisban; Taqwa, Taqwa (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
This study evaluates the reinforcement of religious culture in schools, focusing on the alignment between school vision and mission, the methods used to instill religious values, and the impact on student character development. A qualitative case study approach involved observations, semi-structured interviews, and document analysis. Data were collected from 15 participants, including school administrators, teachers, and students, selected through purposive sampling. Thematic analysis was used to identify patterns and insights regarding religious culture reinforcement. The results indicate that the school’s vision and mission strongly emphasize religious character-building, which is reflected in structured religious activities such as Quran recitations, congregational prayers, and religious discussions. Teachers played a crucial role in modeling religious behavior, reinforcing values through daily interactions. However, student engagement varied; some actively participated while others followed religious programs passively. Additionally, while religious reinforcement positively influenced student discipline, honesty, and respect, some students struggled to maintain these values outside the school environment, highlighting the need for more intrinsic motivation and real-world applications of religious teachings. The study suggests that enhancing interactive religious learning methods, strengthening teacher training programs, and collaborating with families and communities can improve religious culture reinforcement. Future research should explore the long-term sustainability of religious education beyond school settings. This study provides empirical insights into the effectiveness and challenges of religious culture reinforcement in schools, offering practical recommendations for educators, policymakers, and researchers.